The effect of breathing exercises on the anxiety level of preoperative patients in the Dahlia room, dr. Doris Sylvanus Palangka Raya - Henry Wiyono; Prayogae P. Putra (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
Patients who will undergo surgical procedures are generally accompanied by anxiety disorders. As a result of the anxiety disorders experienced by preoperative patients, it is possible that the operation cannot be carried out because symptoms of increased blood pressure will appear. if these measures are continued it can result in difficulty stopping the bleeding. Breathing exercise is a non-pharmacological therapy for treating anxiety that can stimulate the vagus nerve to reduce the hormone cortisol, which is the hormone that causes anxiety. This study aims to determine the effect of breathing exercise on the anxiety level of preoperative patients in Dahlia room, Doris Sylvanus General Hospital, Palangka Raya. This study used a pre-experimental design, with a one group pre-test-post-test design approach, the sampling technique used was consecutive sampling, with a sample of 27 respondents and tested with Wilcoxon statistical techniques. The results of the analysis using the Wilcoxon statistical test obtained p-value, 000 <from 0.05, which means that Ha is accepted, that is, there is an effect of breathing exercise on reducing anxiety levels. It is hoped that the results of this study can be applied by health workers be able to perform breathing exercises as an anxiety therapy